1995
DOI: 10.1074/jbc.270.7.3186
|View full text |Cite
|
Sign up to set email alerts
|

The Major Protein of Messenger Ribonucleoprotein Particles in Somatic Cells Is a Member of the Y-box Binding Transcription Factor Family

Abstract: A cDNA encoding the major core protein, p50, of cytoplasmic messenger ribonucleoprotein particles (mRNPs) of somatic cells was cloned from a rabbit reticulocyte cDNA library. From the derived 324-amino acid sequence, p50 is identified as a member of the Y-box binding transcription factor family. The protein was earlier described as a repressor of globin mRNA translation. These findings suggest that p50 may affect protein biosynthesis at two levels: mRNA transcription in the nucleus and mRNA translation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
147
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 30 publications
10
147
0
Order By: Relevance
“…21 We have shown that YB-1 recognizes the inverted CCAAT box as well as cisplatin-modified DNA. 5 YB-1 is a major core protein of messenger ribonucleoprotein particles, 22 and its overexpression in mammalian cells inhibits protein synthesis. 23 It has been shown to bind specifically to RNA containing 8-oxoguanine, 24 suggesting that it may function to sequester oxidatively damaged mRNA molecules from the translational machinery.…”
Section: Figurementioning
confidence: 99%
“…21 We have shown that YB-1 recognizes the inverted CCAAT box as well as cisplatin-modified DNA. 5 YB-1 is a major core protein of messenger ribonucleoprotein particles, 22 and its overexpression in mammalian cells inhibits protein synthesis. 23 It has been shown to bind specifically to RNA containing 8-oxoguanine, 24 suggesting that it may function to sequester oxidatively damaged mRNA molecules from the translational machinery.…”
Section: Figurementioning
confidence: 99%
“…It is also present in mRNPs derived from polysomes, but in lower amounts (9,10). Regardless of the fact that p50 displayed little or no specificity for RNA in in vitro binding experiments (10,11), in cell extracts, p50 was found only in association with mRNA (12). This protein is located mostly in the cytoplasm, and its amount is ϳ0.1% of the total protein, which corresponds to ϳ5-10 molecules of p50/molecule of mRNA (12).…”
mentioning
confidence: 97%
“…Among all mRNP proteins, p50 is the most basic, with a pI of ϳ9.5 (10). In the absence of RNA, p50 forms large multimeric complexes with a molecular mass of ϳ800 kDa (11). When binding to mRNA, p50 melts up to 60% of the RNA secondary structure (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations